It’s HERstory: Unhealthy Relationships in Adolescence and Subsequent Social and Emotional Development in College Women - Rodenhizer, Kara Anne E. (Violence against women, 2021)
The current study sought to expand our understanding of how early relationships characterized by intimate partner violence (IPV) influence college women’s transition into emerging adulthood. We used a longitudinal qualitative design in which women (n = 13) with histories of IPV victimization participated in interviews twice a year beginning their first semester in college and ending in their final semester of college. Four primary themes were uncovered: making sense of the relationship, recognizing needs in the relationship, posttraumatic growth, and social cognitive maturity. The constitutive pattern across all four themes was resilience (i.e., positive adaptation during and after experiencing adversity).